Characteristics of technical-tactical preparation of Russian men`s judo representation during the Olympic Games in London in 2012 - Adam, M.; Wolska, B.; Klimowicz, P.; Smaruj, M. (Baltic Journal of Health and Physical Activity, 2013)
Background The aim of the study was to determine the value of indices of tactical and technical preparation (PTT) of Russian judo athletes during the Olympic Games in London. The values of these indices may designate the direction of activity in the process of special preparation and in the search for factors to optimize training before the main competitions.